Optimalisasikan Peran Mahasiswa Dalam Pencegahan Stunting Melalui Inovatif Makanan Sehat Gimbab Isi Sayuran Dan Telur - Bunari Bunari; Gilang Arihta; Imelda Purnama; Indah Yuliza; Nurvitasari Nurvitasari; Jones Angga; Puthi Nadia; Fitri Salsabila R; Salsabila Ramadhani; Mifthaurriadh El Ihsani; Budi Gunawan (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
Real work lectures are a synergistic learning program as a form of student service to society. The real work lecture raised the theme of stunting prevention. One of the real work college programs carried out is making innovative food that is healthy and easy for all ages, especially toddlers, to enjoy. An innovative food with basic ingredients of rice, vegetables and eggs is kimbap. Stunting prevention outreach and demonstrations were carried out once at the Village Pendopo targeting toddlers and mothers. The result of this activity is the formation of local kimbap products that toddlers like.